Children's tooth decay in a public health program to encourage low-income pregnant women to utilize dental care - Shirtcliff R Mike; Sutherland Marilynn; Milgrom Peter; Ludwig Sharity; Smolen Darlene (BMC, 2010)
Abstract Background A community-based public health program to provide a dental home for women covered by the Oregon Health Plan (Medicaid) in Klamath County, Oregon USA was instituted with the long-term goal to promote preventive oral care for both mothers and their new infants provided by dental managed care companies. Methods As part of the evaluation of the program, children in Klamath and comparable non-program counties were examined in their 2nd year of life to begin to determine if benefits accrued to the offspring of the mothers in Klamath County. Results Eighty-five and 58.9% of the children were caries free in the Klamath and comparison county samples, respectively (RR = 1.48, 95% CI 1.13, 1.93). The mean (SD) number of teeth with any decay was .75 (2.5) in the test population and 1.6 (2.5) in the comparison population (t = 2.08, p = .04). Conclusions The assessment showed that children of mothers in the Klamath County program were about one and a half times more likely to be caries free than children in the comparison counties. Additional controlled studies are being undertaken.